Representing children’s digital flashcards using rapid serial and visual presentation techniques - Siti Zahidah Abdullah; Nazlena Mohamad Ali; Riza Sulaiman; Mohd Syazwan Baharuddin (Penerbit UKM, 2011)
This research implemented Rapid Serial and Visual Presentation (RS VP) technique to visualize digital flashcard images. Flashcard method is used to provide early exposure for children’s digital learning. This research involves two groups of students (6-8 years old) from typical and LINUS classes. Two main experiments were involved: 1) acceptance of the RSVP, and 2) comparison of difference modes in the RSVP. The results show that the RSVP was positively accepted.There were variations of acceptance amongst each group of students; in terms of performance and concentration. Sixty percent of the students chose the dynamic mode, and 40% chose the static mode. The memory and performance of students using the static mode was better, which the mean scores for the static mode achieved 3.4, higher than the dynamic mode of only 0.7. The significance of this study is to provide an early exposure through digital flashcard learning, using RSVP for children.